Effect of High-velocity Resistance Exercise on 24-h Blood Pressure in Hypertensive Older Women - Oliveira-Dantas, Filipe Fernandes; Browne, Rodrigo Alberto Vieira; Oliveira, Ricardo Santos; Cabral, Ludmila Lucena Pereira; de Farias Junior, Luiz Fernando; Costa, Eduardo Caldas (International Journal of Sports Medicine, 2020)
This study investigated the acute post-exercise effect of high-velocity resistance exercise on ambulatory blood pressure in hypertensive older women. Fourteen volunteers (67.9±5.1 years) performed a high-velocity resistance exercise session (8 exercises using Thera-Band, 3 sets of 6 repetitions as fast as possible in the concentric phase with moderate intensity) and a control session, separated by a 7–10-day period. Ambulatory blood pressure was monitored following 12-h post-sessions and compared between conditions at 1 to 4-h, 5 to 8-h, and 9 to 12-h. Average 24-h ambulatory blood pressure, awake, asleep periods, and blood pressure load were also analyzed. There was a condition by time interaction for systolic ambulatory blood pressure over 12-h post-sessions (P=0.043). It was observed a lower systolic ambulatory blood pressure in the first 4-h period following the high-velocity resistance exercise session compared to the control session (−6.7 mmHg, 95% CI  − 11.6 to −1.8 mmHg; P=0.011). No changes were observed for diastolic ambulatory blood pressure over 12-h post-sessions as well as for the other variables analyzed (P>0.05). In summary, a single high-velocity resistance exercise session elicits a post-exercise antihypertensive effect and may be considered as a strategy to acutely improve blood pressure control in hypertensive older women.
Keywords: post-exercise hypotension; hypertension; resistance training; elderly